PERSAMAAN SUBDIFUSI KONFORMABEL DENGAN PENGARUH KEMOTAKSIS - Bambang Hendriya Guswanto; Muhamad Ichlasul Jihad; Dwiky Octa Yuniarto; Indra Herdiana (Universitas Jenderal Soedirman, 2026)
The research discusses the derivation of the conformable fractional diffusion-chemotaxis equation and the solution of the equation in multidimensional space. The derivation of the diffusion-chemotaxis equation is obtained from a continuous-time random walk process influenced by external factors using conformable fractional derivatives, fractional Laplace transformation, and probability measures on the multidimensional unit sphere . Meanwhile, the solution to the equation is obtained using fractional Laplace transformation and multidimensional Fourier transformation. The mathematical model obtained describes the random movement of particles diffusing and influenced by chemotaxis attraction. Numerical simulations of the solution in one and two dimensions also indicate that the particle movement in conformable diffusion-chemotaxis is slower compared to regular diffusion-chemotaxis.